Commentary: The roles of mothers versus fathers in intergenerational family risk – a commentary on Rothenberg et al. (2023). (23rd December 2022) - Capaldi, Deborah M.; Kerr, David C.R.
Abstract : Basic research studies in the past 2 decades have established that conduct problems and antisocial behavior are associated across generations within families. The Fast Track study represents a major prevention effort with children showing higher levels of conduct problems in childhood, and the Rothenberg et al. ( Journal of Child Psychology and Psychiatry, 2022) study sheds light on whether this intervention has beneficial effects on the family of procreation. In this commentary, we consider the implications of the major finding that such effects were found for women but not for men. We discuss evidence that men's parenting behavior is influenced by the parenting behavior and overall risk of their women partners, and thus preventive interventions in childhood may have beneficial influences on fathers through mothers.